Tingkat Kesehatan Kinerja Keuangan PT. BPR Luhur Damai Kabupaten Tabanan dengan Metode Capital, Asset, Earning, dan Liquidity - DHARMA, I KETUT ARYA BUDI; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Health Level of Financial Performance of PT. BPR Luhur Damai Tabanan Regency with Capital, Asset, Earning, and Liquidity Methods The COVID-19 pandemic has quite an impact on the financial performance of a BPR. PT. BPR Luhur Damai is one of the rural banks in the Tabanan area, which has the potential to be disrupted by its financial performance so that it can cause losses to rural banks. This study aims to determine the level of health of financial performance and the development of the level of health of overall financial performance at PT. BPR Luhur Damai Tabanan Regency with Capital, Asset, Earning, and Liquidity. Methods The results of this study show that: First, the health level of BPR's financial performance is seen from the Capital (CAR) aspect in 2019 – 2021 in the healthy category. In the Asset aspect (KAP) in 2019 and 2020, it is included in the fairly healthy category, and in 2021 in the healthy category. Based on the Earning aspect, the ROA value in 2019 and 2020 is in the fairly healthy category, while in 2021 it is classified as healthy and the BOPO value in 2019, 2020, and 2021 is included in the healthy category. The liquidity aspect (LDR) in 2019 and 2020 is included in the healthy category while 2021 is included in the unhealthy category. Second, the development of the health level of PT. BPR Luhur Damai in 2019, 2020, and 2021 including the healthy category because of its value of more than 81. PT. BPR Luhur Damai in the future is expected to be able to maintain financial performance so that the health level of the BPR is in the healthy category.